Comportamento de tijolos de solo-cimento com adição de escória de alto-forno a esforços de compressão - Paula, Vitor Vezzaro de [UNESP] (Universidade Estadual Paulista (Unesp), 2017)
There has been an ongoing concern over the impact of man's uncontrolled exploitation of the environment. The construction sector-field, responsible for the largest consumption of natural resources and also for most of the disposal tossed into the environment seems to be a promising field of research for engineers, architects and other professionals, who seek the development of more sustainable materials and less aggressive means of production. Unburned (ecological) bricks are one of the answers to this problem. Its composition, use and the elimination of the need of sintering make this product meet the three criteria that makes up the tripod of sustainability: economical, social and environmental. The objective of this paper is to evaluate the technical viability of the manufacturing of these bricks at an industrial level, replacing the cement in 50% concentration by blast furnace slag. The bricks manufactured showed high fragility even after 28 days of its manufacturing, breaking easily even at the beginning of the compression tests. As for the water absorption test, the values were 9.4 p.p. above the maximum limit of 20% as set by ABNT NBR 10833. However, these results do not indicate the unfeasibility of the use of slag as a partial replacement for cement.

É crescente a preocupação com o impacto causado por anos de exploração desenfreada do homem ao meio ambiente. O setor da construção civil, responsável pelo consumo de grande parte dos recursos naturais e também por grande parte dos descartes no meio ambiente, surge como um promissor campo de pesquisa para engenheiros, arquitetos e outros especialistas, que buscam o desenvolvimento de materiais mais sustentáveis e meios de produção menos agressivos. Os tijolos de solo-cimento são uma das soluções. Sua composição, seu modo de utilização e o fato de eliminar a necessidade de sinterização, fazem com que esse produto atenda aos três critérios constituintes do tripé da sustentabilidade: econômico, social e ambiental. O objetivo deste trabalho foi avaliar a viabilidade técnica da fabricação desses tijolos na indústria, substituindo o cimento em teor de 50% por escória de alto-forno. Os tijolos fabricados apresentaram acentuada fragilidade mesmo após 28 dias de sua fabricação, rompendo-se de modo relativamente fácil ainda no início do ensaio de compressão. Quanto ao ensaio de absorção de água, os valores se mostraram 9,4 p.p. acima do limite máximo de 20%, estipulado pela ABNT NBR 10833. Entretanto, esses resultados não indicam a inviabilidade do uso da escória como substituto parcial do cimento.
Behavior of soil-cement bricks with addition of blast furnace slag at compressive stresses
Keywords: Tijolos; Escoria; Construção civil; Material cerâmico; Cimento portland; Bricks